Evaluation of Changes in the Motor Network Following BCI Therapy Based on Graph Theory Analysis - Mazrooyisebdani, Mohsen; Nair, Veena A.; Loh, Po-Ling; Remsik, Alexander B.; Young, Brittany M.; Moreno, Brittany S.; Dodd, Keith C.; Kang, Theresa J.; William, Justin C.; Prabhakaran, Vivek (Frontiers in Neuroscience, 2018)
Despite the established effectiveness of the brain-computer interface therapy (BCI) during stroke rehabilitation [12,13-18], little is understood about the connections between motor network reorganization and functional motor improvements. The aim of this study was to investigate changes in the network reorganization of the motor cortex during BCI therapy. Graph theoretical approaches are used on resting-state fMRI data acquired from stroke patients to evaluate these changes. We also examined correlations between these changes and behavioral measurements. Right hemisphere chronic stroke patients (average time from stroke onset = 38.23 months 46.27 months, n = 13, 6 males, 10 right-handed) with upper-extremity motor deficits received interventional rehabilitation therapy using a closed-loop neurofeedback BCI device. Eyes-closed resting-state fMRI (rs-fMRI) scans, along with T-1 weighted anatomical scans on 3.0T MRI scanners were collected from these patients at four test points. Immediate therapeutic effects were investigated by comparing pre and post-therapy results. Our results displayed the motor network average clustering coefficient increased significantly from pre to post therapy. Furthermore, increased regional centrality of ipsilesional primary motor area (p=0.02) and decreases in regional centrality of contralesional thalamus (p=0.05), basal ganglia (p=0.05 in betweenness centrality analysis and p=0.03 for degree centrality), and dentate nucleus (p=0.03) were observed (uncorrected). This suggests overall a trend towards significance in terms of involvement of these regions. Increased centrality of primary motor area may indicate increased efficiency within its interactive network as an effect of BCI therapy. Notably, changes in centrality of the bilateral cerebellum regions have strong correlations with clinical variables.